2013
DOI: 10.1016/j.rmed.2013.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Survival after lung transplantation in systemic sclerosis. A systematic review

Abstract: The short-term and intermediate-term survival post-lung transplantation are similar to IPAH and ILD patients requiring lung transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 32 publications
3
36
0
3
Order By: Relevance
“…The short-and intermediate-term survival of SSc-ILD patients post-lung transplantation are similar to those seen in idiopathic pulmonary fibrosis [86]. Considering the main studies on lung and heart-lung transplantation an overall survival of 52-80% at 2 years is reported [87][88][89][90].…”
Section: Lung Transplantationsupporting
confidence: 53%
“…The short-and intermediate-term survival of SSc-ILD patients post-lung transplantation are similar to those seen in idiopathic pulmonary fibrosis [86]. Considering the main studies on lung and heart-lung transplantation an overall survival of 52-80% at 2 years is reported [87][88][89][90].…”
Section: Lung Transplantationsupporting
confidence: 53%
“…Thus relatively fewer lung transplantations have been performed for these patients than for patients with other diseases (13). Many studies have indicated similar survival rates for these patient groups (13,14,16,(20)(21)(22)(23)(24)(25)(26). Among the studies comparing the survival rates between patients with CTD-ILD and those with other diseases who underwent lung transplantation, Takagishi et al reported survival outcomes for CTD patients and patients with chronic obstructive pulmonary disease (COPD) and IPF after lung transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there have been few studies of CTD-ILD patients undergoing lung transplantation in Asia (13,(16)(17)(18).…”
Section: Original Articlementioning
confidence: 99%
“…No hay estudios controlados con asignación aleatoria, pero un metaanálisis reciente muestra que la supervivencia de estos pacientes puede ser igual a la de los trasplantados por otras causas siempre y cuando sean seleccionados cuidadosamente (52).…”
Section: Nuevos Tratamientosunclassified